Hubungan Status Gizi, Status Ekonomi dan Akses Media Informasi dengan Status Menarche pada Remaja di SMPN 8 OKU Tahun 2021 - Sri Hartatik; Rohaya Rohaya; Turiyani Turiyani (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Menarche is the first menstrual period that occurs when a woman enters puberty. Many factors influence menarche including nutritional status, economic status and access to information media. The purpose of this study was to determine the relationship between nutritional status, economi status and access to media information simultaneously with adolescent menarche status at SMPN 8 OKU. This research method is an analytic survey method with a cross sectional design. The population of 181 young women and the research sampel amounted to 70 young women who were taken from the inclusion criteria and exclusion criteria using purposive sampling technique. The research instrument used a questionnaire, weight and height measuring instrument to measure nutritional status, economic status and access to media. Of all 65,7% adolescents experienced normal menarche. Data analysis was performed using the chi square test, with a significance level of 0,05. The results of statistical tests on nutrional status related to menarche status with a p value of 0,002, economi status related to menarche status with a p value of 0,023, media access to information related to menarche status with a p value of 0,015. The results of this study are expected to be a reference for other researhers and health workers to pay more attention to and improve the health of young women.